Scholars' guide to Washington, D.C., for East Asian studies : - Kim, Hong N. (Smithsonian Institution Press, 1979)
This volume on East Asia is designed to serve the specific needs of scholars who are interested in knowing the scope of research facilities and resource on the region available in the nation's capital.